2016
DOI: 10.5897/ajmr2015.7923
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance of Enterococci isolated from raw camel milk in the South West of Algeria

Abstract: Little information is available on the diversity and distribution of resistance and virulence factors in Enterococci isolated from camel milk. In this study, 33 samples of camel's milk collected from the south west region of Algeria were analyzed for the presence of Enterococcus spp. Twenty three (23) enterococcal isolates were recovered. These strains were identified by the API 20 STREP and the sodium dodecyl sulphate-polyacramide gel electrophoresis (SDS-PAGE) of whole cell protein at the species level: Ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Comparing these results with the literature, we find that they are higher than those found in Egypt for tetracycline (65%), chloramphenicol (1.6%), 13 penicillin (0%) 17 and lower than those found for streptomycin (78%), erythromycin (40%), ciprofloxacin (15%), gentamicin (55%), and vancomycin (5%) in raw milk cheese. 13 Other studies in Morocco have shown that the following Enterococcus spp.…”
Section: Discussionsupporting
confidence: 52%
“…Comparing these results with the literature, we find that they are higher than those found in Egypt for tetracycline (65%), chloramphenicol (1.6%), 13 penicillin (0%) 17 and lower than those found for streptomycin (78%), erythromycin (40%), ciprofloxacin (15%), gentamicin (55%), and vancomycin (5%) in raw milk cheese. 13 Other studies in Morocco have shown that the following Enterococcus spp.…”
Section: Discussionsupporting
confidence: 52%
“…Growth characteristics were tested in de Man-Rogosa-Sharpe agar (MRS) and Citrate Azide agar (CA) (Domig, 2003;Naceur & Boudjemâa, 2016). Based on catalase-negative and grampositive, the suspected Enterococci were isolated and identified as presumptive Enterococci.…”
Section: Isolation and Identification Of Enterococcimentioning
confidence: 99%